Physicochemical, Nutrient, and Biological Water Quality Data from Lacustrine Systems of the Yucatán Peninsula during the Dry Season (April 2024) - Plutarco Hernández Hernández (PANGAEA, 2026)
This dataset contains physicochemical, nutrient, and biological measurements of surface waters collected from multiple lacustrine systems across the Yucatán Peninsula during the dry season (April 2024). Sampling sites were distributed across inland lakes and lagoons within a karstic low-relief landscape strongly influenced by the regional aquifer system. In situ measurements included water temperature, electrical conductivity, pH, dissolved oxygen concentration, oxygen saturation, and turbidity, obtained using a calibrated multiparameter probe. Additional laboratory analyses were conducted to determine total dissolved solids, biochemical oxygen demand, total nitrogen, total phosphorus, chlorophyll-a concentration, and total coliform bacteria. Geographic coordinates and sampling dates were recorded for each site. Derived indicators such as the Carlson Trophic State Index (TSI) and the Water Quality Index (WQI) were calculated to provide an integrated assessment of trophic status and overall water quality. The dataset provides a regional snapshot of limnological conditions during the dry season and offers a baseline for assessing spatial variability, eutrophication status, and water quality patterns in inland aquatic ecosystems of the Yucatán Peninsula.